2010
DOI: 10.1128/jb.01240-09
|View full text |Cite
|
Sign up to set email alerts
|

Global Regulation of Gene Expression and Cell Differentiation inCaulobacter crescentusin Response to Nutrient Availability

Abstract: In a developmental strategy designed to efficiently exploit and colonize sparse oligotrophic environments, Caulobacter crescentus cells divide asymmetrically, yielding a motile swarmer cell and a sessile stalked cell. After a relatively fixed time period under typical culture conditions, the swarmer cell differentiates into a replicative stalked cell. Since differentiation into the stalked cell type is irreversible, it is likely that environmental factors such as the availability of essential nutrients would i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
42
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 61 publications
4
42
0
3
Order By: Relevance
“…A recent study of the C. crescentus response to carbon starvation identified 154 genes that are induced (7). A total of 112 of these genes showed at least partial rpoN dependence, suggesting a significant role for 54 in Caulobacter's transcriptional response to carbon starvation (7). Many of the 42 rpoN-independent and carbon starvation-induced genes identified in that study overlap with the CrfA-regulated genes described here.…”
mentioning
confidence: 57%
See 3 more Smart Citations
“…A recent study of the C. crescentus response to carbon starvation identified 154 genes that are induced (7). A total of 112 of these genes showed at least partial rpoN dependence, suggesting a significant role for 54 in Caulobacter's transcriptional response to carbon starvation (7). Many of the 42 rpoN-independent and carbon starvation-induced genes identified in that study overlap with the CrfA-regulated genes described here.…”
mentioning
confidence: 57%
“…The product of the SpoT enzyme, ppGpp has been shown to play a key role in regulating the initiation of DNA replication during carbon starvation as well as enabling longterm survival in medium lacking a carbon source (16). Finally, microarray studies on carbon-deprived cells have identified a number genes encoding TonB-dependent receptors, carbon source catabolic enzymes, and transcriptional regulators whose expression is strongly upregulated during carbon starvation (7). The alternative sigma factor 54 encoded by rpoN was shown to be necessary for the complete induction of many of these genes (7).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The Gram-negative bacterium Caulobacter crescentus can be isolated from freshwater environments and is capable of growing under low-nutrient conditions (32,33). To colonize this type of environment, C. crescentus cells have different types of adaptations.…”
mentioning
confidence: 99%